Climate And Society : Climate As Resource, Climate As Risk. (World Scientific, 2009)
Climate and Society presents from a transdisciplinary view, climate and its changes, impact and perception. The history of climate and its different approaches over time - which are anthropocentric and more system-oriented, academic and application-driven - are reviewed, as are the possibilities of managing climate, in particular by steering the greenhouse gas emissions. Most importantly, the concepts of climate as a resource for societies are discussed and the emergence of climate non-constancy and its impact, studied. In essence, this book provides an absorbing account of the cultural histor.